2015
DOI: 10.3126/jpahs.v1i2.16641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yale observation scale to detect serious bacterial infection in febrile children aged one to 36 months

Abstract: Introductions:In most children aged 1-36 months, the cause of a febrile illness is a self limiting viral infection. It is very difficult to distinguish these from serious bacterial infection. Objective of this study is to assess the efficacy of the Yale Observation Scale (YOS) to detect serious bacterial infection in febrile children aged 1-36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Similar results were found in kansakar P et al, and Bang et al, with 59% and 59.36% respectively of male children. 5,15,16 Since male is the preferred gender in India and more number of male children are brought to health care services, so this may be the reason of higher preponderance of male over female in the present study.…”
Section: Resultsmentioning
confidence: 79%
“…Similar results were found in kansakar P et al, and Bang et al, with 59% and 59.36% respectively of male children. 5,15,16 Since male is the preferred gender in India and more number of male children are brought to health care services, so this may be the reason of higher preponderance of male over female in the present study.…”
Section: Resultsmentioning
confidence: 79%
“…Kansakar et al have found that 33% children were suffered from SBI in their study population. 21 Serious bacterial illness(SBI) contribute to 33% of cases while the commonest cause of SBI was pneumonia. This observation issimilar to a study done by McCarthy et al 22 It was observed that the sensitivity (87.7%) and specificity (70.6%) were higher in YOS >12 to detect SBI.…”
Section: Discussionmentioning
confidence: 99%